Konsep Kempel dalam Keprakan dan Dhodhogan pada Pergelaran Wayang Golek Menak Gaya Yogyakarta - Sukistono, Dewanto (Institut Seni Indonesia Yogyakarta, 2022)
ABSTRACT The Concept of Kempel in Keprakan and Dhodhogan in Yogyakarta-style Menak Wooden Puppet Show. KKeprakan and dhodhogan are two of the accompaniments in Menak wooden puppet show in Yogyakarta. The term keprakan is derived from the essential word ‘keprak’ which refers to the principle of form, material, variety, and technique of creating sounds from the iron plates pounded by using cempala made from iron or wood. The term dhodhogan is taken from the root ‘dhog’ which refers to the sound produced by iron or wood that is pounded on kothak. The term kempel has meaning as ‘whole’ and ‘blend into one’. Further, in the context of keprakan, its meanings is that the sound created is harmonically integrated with the movement of the puppet and the motif of kendhangan. This study aims to disclose the pattern of keprakan and dhodhogan to produce a sense of kempel in supporting the aesthetic expression of puppet characters and the scenes’ ambiences. The author collected the data through direct participation, in-depth interviews, and observations of recordings of Menak puppet show in which Sukarno as the puppeteer. The data analysis was conducted to draw a conclusion as a result of an investigation of the relationship among the pattern of both keprakan and dhodhogan; the movement diversity of puppet characters; and the motif of kendhangan. According to the results, it can be stated that the design of keprakan and dhodhogan in Menak wooden puppet show in Yogyakarta consists of two styles – the one is free style and the other is bound style. The sense of kempel lies in the accuracy of keprakan and dhodhogan diverse sound combinations in relation to the movement varieties of puppet figures incorporated with the motif of kendhangan.ABSTRAK Keprakan dan dhodhogan adalah salah satu bagian dari iringan pergelaran wayang golek Menak gaya Yogyakarta. Istilah keprakan dari kata dasar keprak menunjuk pada persoalan bentuk, bahan, ragam, serta teknik menghasilkan bunyi dari lempengan besi yang dipukul menggunakan cempala berbahan besi maupun kayu. Istilah dhodhogan diambil dari kata dasar dhog yang menunjuk pada bunyi yang dihasilkan cempala besi atau kayu yang dipukul pada kothak. Kosa kata kempel mempunyai makna utuh dan melebur menjadi satu, dalam konteks keprakan maknanya bahwa bunyi yang dihasilkan menyatu dengan gerak wayang dan motif kendhangan. Penelitian ini bertujuan untuk mengungkap pola keprakan dan dhodhogan untuk menghasilkan rasa kempel dalam mendukung ekspresi estetis tokoh wayang maupun suasana adegan. Data diperoleh melalui partisipasi terlibat, wawancara mendalam, serta pengamatan terhadap rekaman pergelaran wayang golek Menak dengan dalang Ki Sukarno. Analisis dilakukan untuk mendapatkan simpulan berdasarkan telaah terhadap relasi antara pola keprakan dan dhodhogan dengan ragam gerak tokoh wayang serta motif atau pola kendhangan. Berdasarkan hasil penelitian dapat dijelaskan bahwa pola keprakan dan dhodhogan dalam pergelaran wayang golek Menak gaya Yogyakarta terdiri dari dua ragam, yaitu ragam bebas dan ragam berpola. Rasa kempel terletak pada ketepatan dalam memadukan ragam bunyi keprakan dan dhodhogan sesuai dengan ragam gerak tokoh wayang yang menyatu dengan motif kendhangan.